The concept of procedural stage: traditional approaches and controversial innovations - Marchenko, V. B. (Науковий вісник Ужгородського національного університету. Серія Право, 2025)
This article explores the problematic aspects of introducing the concept of a «stage of delivering a court decision» into the non-criminal procedural codes of Ukraine – namely, the Commercial Procedural Code, the Civil Procedural Code, and the Code of Administrative Procedure. The principal aim is to assess whether this legislative innovation and conceptual novelty are appropriate: whether they fit into the normative procedural system and whether they correspond to the established understanding of procedural law regarding the structure of judicial proceedings and the content of its elements – particularly, the concept of a procedural stage. A systematic and normative analysis is conducted using the Commercial Procedural Code of Ukraine as a primary example. The article examines how the term “stage” is used in legal scholarship on procedural law. The author argues that procedural legislation should be built upon a scientifically grounded understanding of the procedural stage as a special legal concept, rather than as a colloquial expression. An original definition of «procedural stages» is proposed. The article presents an author’s position on the introduction of the «stage of delivering a court decision» as a separate procedural stage and normative concept. This position maintains that the chosen legislative form of the innovation is unsuccessful. While aiming to resolve one issue, the legislature has introduced another, which distorts one of the core procedural concepts – the notion of a procedural stage. The new provision fails to meet the structural, formal-logical, systemic-functional, and substantive criteria of a genuine procedural stage. It is only a nominal imitation, lacking scientific accuracy and internal coherence. Delivering a court decision, as a procedural phenomenon, should be regarded as a procedural act – possibly as a phase within the substantive hearing stage – but not as an independent procedural stage. Neither doctrinal theory nor normative logic supports such classification. As a conclusion, the article proposes amendments to procedural codes to align the concept of procedural stage with academically grounded criteria.